2013
DOI: 10.1158/0008-5472.can-12-4617
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modeling of Cancer Cell Signaling Pathways Enables Systematic Drug Repositioning for Distinct Breast Cancer Metastases

Abstract: A new type of signaling network element, called cancer signaling bridges (CSB), has been shown to have the potential for systematic and fast-tracked drug repositioning. On the basis of CSBs, we developed a computational model to derive specific downstream signaling pathways that reveal previously unknown target–disease connections and new mechanisms for specific cancer subtypes. The model enables us to reposition drugs based on available patient gene expression data. We applied this model to repurpose known or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Our previously published gene expression data of breast CSCs (CD44 + /CD24 −/low and MS‐forming treatment‐resistant cells) was used for in silico drug repositioning analysis (GSE7513, SE7515, and GSE10281) . The cancer signaling bridges (CSBs)‐based drug repositioning computational modeling method was applied to derive specific CSCs signaling pathways .…”
Section: Methodsmentioning
confidence: 99%
“…Our previously published gene expression data of breast CSCs (CD44 + /CD24 −/low and MS‐forming treatment‐resistant cells) was used for in silico drug repositioning analysis (GSE7513, SE7515, and GSE10281) . The cancer signaling bridges (CSBs)‐based drug repositioning computational modeling method was applied to derive specific CSCs signaling pathways .…”
Section: Methodsmentioning
confidence: 99%
“…To date, various computational methods have been developed for drug repositioning classified as target-based [35], knowledge-based [68], signature-based [911] and network-based [12, 13] approaches. While these methods have contributed much to drug discovery, the space of innate human metabolite has relatively not been considered in those approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cancer research, in the last years it has found valuable support in a wide range of modeling and simulation approaches, which cover a wide spectrum ranging from mathematical models -e.g., continuous models [2][3][4] [17]. These approaches have allowed the in silico experimentation in cancer at the cellular, system and patient level.…”
Section: Bodymentioning
confidence: 99%
“…Regarding cancer research, in the last years it has found valuable support in a wide range of modeling and simulation approaches, which cover a wide spectrum ranging from mathematical models -e.g., continuous models [2][3][4] and stochastic models [5][6][7][8] to computational models -e.g., Monte Carlo method and cellular automata [9][10][11], Boolean networks [12], Petri nets [13], artificial neural networks [14][15][16] and expert systems [17]. These approaches have allowed the in silico experimentation in cancer at the cellular, system and patient level.…”
Section: Bodymentioning
confidence: 99%